Adaptasi Komunikasi Lintas Budaya antara Staf Kapal Feri MV Putri Anggreni dengan Penumpang Internasional pada Rute Batam - Johor - Najib; Hakim, Lukman (Indra Institute Research & Publication, 2026)
This study aims to understand forms of cross-cultural communication adaptation between the crew of the MV Putri Anggreni ferry and international passengers on the Batam–Johor route. A qualitative approach with a phenomenological method was employed to explore the lived experiences of individuals involved in intercultural service interactions within international maritime transportation. Research data were collected through in-depth interviews with ferry crew members and Malaysian international passengers, as well as participatory observation conducted during onboard service activities. The findings indicate that differences in language, communication styles, and norms of politeness constitute the main sources of cross-cultural communication barriers. To address these challenges, both crew members and passengers adapt through the use of mixed languages (Indonesian–Malay–English), reliance on nonverbal communication such as gestures and facial expressions, and the application of empathy in service delivery. These adaptive practices help create more effective interactions and reduce the potential for intercultural misunderstandings. This study concludes that cross-cultural communication competence is essential for enhancing public service quality, particularly in international maritime transportation contexts characterized by intensive multicultural interactions.